Physio-chemical and Thermal Characterization of Demineralized Poultry Litter using Mechanical Sizing Fractioning, Acid Solvents, and Deionized Water - Nyoni, Kevin; Kelebopile, Leungo (Journal of Chemistry and Environment, 2023)
Poultry litter is an organic waste composed of manure, feathers, and bedding, containing both organic and inorganic elements. Inorganic elements corrode and agglomerate the reactors when poultry litter is thermally converted to biochar, bio-oil or combusted. Demineralizing poultry litter through mechanical size fractioning, acid solvent, and deionized water can decrease the inorganic elements' composition. This study investigates to identify the effects of different demineralization methods on the physio-chemical and thermal characteristics of poultry litter. Statistical analysis (p-value of 0.001) showed that the pretreatment methods reduced the inorganic elements. Mechanically fractioned poultry litter with particle sizes of 1.19-2.36mm and 2.37-5.00mm showed a low inorganic element composition of 7.85% and 9.19% when demineralized. The acid solvent and PL:DI treatments varied their extraction effectiveness depending on the type of inorganic element removed, ranging from 9.65-11.73% of the total inorganic element composition. PL:AcOH treatment had the lowest ash content at 6.89% from 12.33%. Mechanical size fractioned samples had the lowest moisture content, ranging from 2.53% to 4.65%. All the samples had high fixed carbon content except for PL:<1.18mm sample. Volatile matter for PL: AcOH, PL: DI, and PL:2.37-5.00mm samples were higher than the UT: PL and other treated samples. The treated samples noted a low C, high O, S, N, H/C, and O/C and comparable H content with UT: PL sample. Removal of inorganic elements increased the sample's high heating value, with the PL:2.37-5.00mm sample having the highest at 17.60 MJ Kg-1. The FTIR spectra of the demineralized sample revealed a reduction in the transmittance band, indicating the decomposition of the cellulose and hemicellulose structures. TGA-DTG supported the findings by noting a shift in temperature increase with peak temperatures higher than UT: PL sample samples. The degradation occurred at temperatures up to 380°C, noting the degradation of the cellulose and hemicellulose structure of the demineralized poultry litter.